Perhitungan VEV dari operator Wilson Loop Unknot dari teori Chern-Simons-Witten (CSW) 2+1 dimensi dengan menggunakan teori Braiding dan teori medan kuantum - Asep Yoyo Wardaya (Youngster Physics Journal, 2017)
Concepts of Mathematical (Group theory) and Physics (Quantum Field Theory) sciences have a relationship in many Scientific applications. One example of this relationship is topology field theory such as Jones and HOMFLY polinomials in two space and one time dimensions, which have a connection with the concept of the quantum field theory. In this paper, we investigated  the value of the invarians polynomial at SO(5) group by using braiding group concept that has exact solution. As comparison, Quantum Field Theory concept will be calculated the Vacuum Expectation Value (VEV) of the Wilson loop unknotted operator in Chern-Simons-Witten theory (CSW) 2+1 dimension at the same group that has a convergent power series solution from order 1 / kn (k is a coupling contant). From comparison calculation of invariant polynomial and VEV of SO(5) group, we have the identical result  of them up to 1 / k3 order.Keywords : Invarians Polynomial, CSW, Wilson loop operator, SO(5).